THE ROLE AND IMPORTANCE OF INFORMATION TECHNOLOGIES IN EDUCATION - Botirova Nigora Odilovna; Umirzaqova Sarvinoz Mashrab qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
It is known that information and communication technologies are related to discoveries in the fields of microelectronics, computing (hardware and software), electronic communications and antoelectronics-microprocessors, semiconductors, and optical fiber cables. These discoveries allow the development and storage of vast amounts of information and their rapid distribution through communication networks. Connecting computers and configuring them to communicate with each other allows creating a new powerful technological system, network information systems using a common protocol. They connect people, their homes and offices and develop and execute a huge number of tasks in a very short time. This will fundamentally change the nature of information use and the structure of communication. At the same time, computer networks allow communication with all points of the Earth. For the educational system, it creates new opportunities for communication between teachers and students.